11(v+4)-2v=3(3v+3)-13

Simple and best practice solution for 11(v+4)-2v=3(3v+3)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(v+4)-2v=3(3v+3)-13 equation:



11(v+4)-2v=3(3v+3)-13
We move all terms to the left:
11(v+4)-2v-(3(3v+3)-13)=0
We add all the numbers together, and all the variables
-2v+11(v+4)-(3(3v+3)-13)=0
We multiply parentheses
-2v+11v-(3(3v+3)-13)+44=0
We calculate terms in parentheses: -(3(3v+3)-13), so:
3(3v+3)-13
We multiply parentheses
9v+9-13
We add all the numbers together, and all the variables
9v-4
Back to the equation:
-(9v-4)
We add all the numbers together, and all the variables
9v-(9v-4)+44=0
We get rid of parentheses
9v-9v+4+44=0
We add all the numbers together, and all the variables
48!=0
There is no solution for this equation

See similar equations:

| 8+4x=x | | 16x-1=5(3x+2)-9 | | 3x-8=5x14 | | F(x)=-10x2 | | 0.5(x+3)-0.7(x+3)=-0.2-0.6 | | x+10=-x | | 21x-11=5(4x+4)-9 | | 12+2=14x | | −17−1,3x=35,8+3,1x. | | x*2.5=3.5 | | -9(v+4)+4v+6=8v+12 | | 5x+20x+3x-50=360 | | x2+4=A | | 12*(x-3)-2*(x-1)=10 | | -9(v+2)+3v+6=8v=6 | | 3(x-4)=8-x | | (3x+1)=(14x-25) | | 4*(x-2)=8*x-1*(x+1) | | 9+7a=3(a-5) | | -3(5x-2)=-27-4x | | (6z+1)+(10z)=-31 | | 9-2x=6x+17 | | 4{6-(-8x-5)}=288x+204 | | -5+6x-7x=11+x | | |2x-1|=7; | | -5+6x-7=11+x | | 4(6-(-8x-5))=288x+204 | | (5x-40)=3x | | 6.3=x-5.9 | | x/(-2)=5; | | 0,99726027397260273972602739726027^x=0.5 | | -q+3q=-7+q |

Equations solver categories